Carp Seed Production Factors in India - Das, Rabindra Nath; Shit, Amar Nath; Ghosh, Apurba Ratan (Journal of Environments, 2015)
The carp seed production process is a continuum. In practice, it is too difficult to strictly divide rural from entrepreneurial fish seed producers. Generally, the farmers who have been involved in subsistence level carp seed production increased their production over the years, with the more inputs and better management skill, resulting in enlarging their resource base and gradually becoming entrepreneurial. This report examines the factors which have statistical significant effects on crap seed production. Objective: The responsible factors for carp seed production are varied in nature, and these are not clearly well-known in the literature. Fisheries research often seeks to identify a causal relationship between the fish seed production and the environmental/controlled factors. This article studies three different subject groups (Rohu (24), Mrigal (21) and Catla (12)) for identifying the causal factors of carp seed production. Results: The causal factors of carp seed production are identified here. Statistical significant causal factors for Mrigal are female fish age (P = 0.01), her weight (P< 0.01), size (P = 0.07), 1st-dose (P < 0.01), male fish weight (P < 0.01). For Rohu, significant factors are female fish age (P < 0.01), her weight (P< 0.01), 1st-dose (P = 0.01), 2nd-dose (P < 0.01). For Catla, significant factors are female fish age (P < 0.01), her weight (P< 0.01), 1st-dose (P = 0.01). Effects of these factors on carp seed production are identified. Conclusions: Impacts of female fish age, her weight, size, 1st-dose, male fish weight, 2nd-dose etc., on carp seed production are explained based on mathematical relationships. The present findings support many earlier research outputs. However, these analyses also identify many additional casual factors that explain the means and variances of carp seed production, which earlier researches have not reported.